Terraria Gigantica : The World under Glass - Fritz, Dana, 1970- (Book collections on Project MUSE., 2017)
In a new approach to environmental photography, Dana Fritz explores the world's largest enclosed landscapes: Arizona's Biosphere 2, Cornwall's Eden Project, and Nebraska's Lied Jungle and Desert Dome at the Henry Doorly Zoo.